Inhibition of RtTg neurons reverses methamphetamine-induced attention deficits - Xiaotian Qu; Pingyuan Yang; Rongwei Zhai; Zhi-Qi Xiong (Acta Neuropathologica Communications)
Abstract Chronic methamphetamine (METH) use, a prevalent psychostimulant, is known to impair attention, yet the cellular mechanisms driving these deficits remain poorly understood. Here, we employed a rat model of repeated passive METH injections and evaluated attentional performance using the 5-choice serial reaction time task (5-CSRTT). Using single-nucleus RNA sequencing, immunofluorescence and in situ hybridization, we characterized the response of neurons in the reticulotegmental nucleus (RtTg) to METH exposure. Our results indicate that METH exposure disrupts RtTg neurons at the transcriptional level and results in an increased activation ratio of RtTg under 5-CSRTT conditions. Crucially, chemogenetic inactivation of these neurons or RtTg lesion attenuated METH-induced attention deficits, whereas their activation reproduced the deficits. These findings underscore the critical role of RtTg neurons in mediating METH-induced attention deficits, positioning RtTg as a promising therapeutic target for the treatment of attention deficits linked to chronic METH use.